2020
DOI: 10.1186/s13075-020-2125-2
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and effectiveness of peficitinib (ASP015K) in patients with rheumatoid arthritis: interim data (22.7 months mean peficitinib treatment) from a long-term, open-label extension study in Japan, Korea, and Taiwan

Abstract: Background: Peficitinib (ASP015K), a novel oral Janus kinase inhibitor, has demonstrated efficacy and safety for the treatment of rheumatoid arthritis (RA) in randomized, controlled trials of up to 52 weeks' duration. However, safety and effectiveness after long-term treatment have not been assessed. Methods: This was an interim analysis of an ongoing open-label, multicenter extension study in RA patients who completed phase 2b (RAJ1; 12 weeks) and phase 3 (RAJ3 and RAJ4; 52 weeks) peficitinib studies in Asia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 17 publications
4
30
0
2
Order By: Relevance
“…Notably, 5 of the 90 patients switched from the placebo to peficitinib developed herpes zoster after the treatment change. In the Phase 3 RAJ4 study [21], the incidence of adverse events during the 12 weeks of double-blinded phase was 49.4% in the placebo group and 55.5% in the peficitinib 100 mg and 150 mg groups. During the 52-week study period, herpes zoster was documented in 12 patients in the peficitinib group, and in 2 of the 148 patients switched from placebo to peficitinib post switching.…”
Section: Safety Of Peficitinibmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, 5 of the 90 patients switched from the placebo to peficitinib developed herpes zoster after the treatment change. In the Phase 3 RAJ4 study [21], the incidence of adverse events during the 12 weeks of double-blinded phase was 49.4% in the placebo group and 55.5% in the peficitinib 100 mg and 150 mg groups. During the 52-week study period, herpes zoster was documented in 12 patients in the peficitinib group, and in 2 of the 148 patients switched from placebo to peficitinib post switching.…”
Section: Safety Of Peficitinibmentioning
confidence: 99%
“…To date, results from five randomized, placebo-controlled trials and two long-term extension studies have been reported [15][16][17][18][19][20][21]. Among the five randomized, placebo-controlled trials, two were Phase 2b trials conducted as global studies, one was a Phase 2b trial and one a Phase 3 trial both conducted in Japan, and one was a Phase 3 trial conducted in Japan, Korea, and Taiwan.…”
Section: Efficacy Of Peficitinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of these JAKs offers an alternative treatment approach for RA, principally for those failing initial treatment with methotrexate (MTX) or other csDMARDs [7]. Peficitinib (ASP015K) is an oral pan-JAK inhibitor, which has demonstrated efficacy in Phase 2b and Phase 3 studies, and in a long-term extension (LTE) study, by reducing symptoms of RA and suppressing joint destruction in Asian patients with active RA, at doses up to 150 mg/day [8][9][10][11]. It has also been shown to have an acceptable safety profile for a period of up to 6 years [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Correction to: Safety and effectiveness of peficitinib (ASP015K) in patients with rheumatoid arthritis: interim data (22.7 months mean peficitinib treatment) from a long-term, open-label extension study in Japan, Korea, and Taiwan Following publication of the original article [1], the authors identified an error in the 95% CI bars plotted on the graphs of Fig. 6a, b, and c. The CI numbers in the table below the graph are correct, but the upper and lower limit bars plotted on the graph are incorrect.…”
mentioning
confidence: 99%